Hubungan Tingkat Pengetahuan Dengan Kecemasan Penderita Kanker Terhadap Paparan Virus COVID-19 Di RSKD Jakarta - Muharani, Indah; Fitriana Suprapti; Ainum Jhariah (Journal of Pubnursing Sciences, 2023)
Background:  The COVID-19 caused by SARS-CoV-2 has been claimed as pandemic status by WHO. Although many countries have categorized this pandemic into endemic status; the thought of exposed to this virus made them anxious, especially for individuals suffering from chronic diseases such as cancer. Purposes:  This study aimed to determine the relationship between the knowledge and anxiety levels of cancer patients on COVID-19 exposure at the National Cancer Referral Hospital in 2021. Method: This study was a quantitative study with a descriptive correlative design and a cross-sectional approach. The sample in this study was 86 cancer patients aged at least 20 years old from all cancer categories using a purposive sampling technique. Result:  Univariate results showed that the majority of respondents aged >40 (76.7%) and college education level (47.7%) with good knowledge level (74.4%) and a low anxiety level (51.2%). Bivariate analysis using the Chi-square test with = 0.05 showed there was no significant relationship between the level of knowledge and anxiety (p-value 0.192).  Conclusion: COVID-19 can affect a person's anxiety level. Researcher's suggestions: It is hoped that cancer patients will receive health education and look for sources of information related to COVID-19.